DEVELOPING COUNTRIES’ RESPONSE TO THE CLEAN DEVELOPMENT MECHANISM UNDER IMPERFECT INFORMATION AND TRANSACTION COSTS - HONLONKOU, N'lédji Albert; HASSAN, Rashid (My University, 2015)
Developing countries are struggling for finding resources to finance their adaptation to or mitigation of the effects of climate change. In that spirit, the Copenhagen summit, the fifteenth Conference of Parties (COP15) can be seen as a success since it ended with an important promise of creation of a common fund of $US 100 billions per year over the period 2013–2020 to help poor and emerging countries to support adoption of costly but eco-friendly technologies. However, implementation of former instruments shows mixed results. In this paper, we show that transaction costs effect dominates asymmetric information effect in impeding some de- veloping countries to benefit from the clean development mechanism, one of the instruments of the implementation of the Kyoto Protocol. Thus environmental instruments may be useless if they are not supplemented by policies to reduce transaction costs in the host countries.
Keywords: Climate change; clean development mechanism; information asymmetry; transaction cost; developing countries